Using institutional theory to analyse hospital responses to external demands for finance and quality in five European countries. (April 2016) - Burnett, Susan; Mendel, Peter; Nunes, Francisco; Wiig, Siri; van den Bovenkamp, Hester; Karltun, Anette; Robert, Glenn; Anderson, Janet; Vincent, Charles; Fulop, Naomi
Objectives: Given the impact of the global economic crisis, delivering better health care with limited finance grows more challenging. Through the lens of institutional theory, this paper explores pressures experienced by hospital leaders to improve quality and constrain spending, focusing on how they respond to these often competing demands. Methods: An in-depth, multilevel analysis of health care quality policies and practices in five European countries including longitudinal case studies in a purposive sample of ten hospitals. Results: How hospitals responded to the financial and quality challenges was dependent upon three factors: the coherence of demands from external institutions; managerial competence to align external demands with an overall quality improvement strategy, and managerial stability. Hospital leaders used diverse strategies and practices to manage conflicting external pressures. Conclusions: The development of hospital leaders' skills in translating external requirements into implementation plans with internal support is a complex, but crucial, task, if quality is to remain a priority during times of austerity. Increasing quality improvement skills within a hospital, developing a culture where quality improvement becomes embedded and linking cost reduction measures to improving care are all required.